Delivery of remote otology care: a UK pilot feasibility study. Issue 1 (8th February 2022) - Forde, Cillian T; Dimitrov, Lilia; Doal, Suneal; Patel, Jay; Clare, Dawn; Burslem, Michael; Mehta, Nishchay; Manjaly, Joseph G
Abstract : Introduction: The COVID-19 pandemic has catalysed the need to implement the National Health Service Long-Term Plan to deliver more care in the community and to reduce face-to-face hospital appointments by up to 33%. This study aimed to assess the feasibility of a remote otology service from triage through to delivery. Methods: New adult otology referrals at a tertiary ear, nose and throat (ENT) hospital aged between 18 and 70 with hearing loss or tinnitus were included. Patients attended an audiology-led community clinic where they underwent a focused history, audiometric testing, and a smartphone-based application and otoscope (Tympa System) was used to capture still and video images of their eardrums. The information was reviewed by ENT clinicians using a remote review platform with a subset of patients subsequently undergoing an in-person review to measure concordance between the two assessments. Results: 58 patients participated. 75% of patients had their pathways shortened by one hospital visit with 65% avoiding any hospital attendances. 24% required an additional face-to-face appointment due to incomplete views of the tympanic membrane or need for additional examinations. Electronic validation by a blinded consultant otologist demonstrated a diagnosis concordance of 95%, and concordance between remote-review and in-person consultations in the 12 patients who agreed to attend for an in-person review was 83.3%. 98% of patients were satisfied with the pathway. Conclusion: This pilot service is feasible, safe and non-inferior to the traditional outpatient model in the included patient group. There is potential for the development of a community audiology-led service or use for general practioner advice and guidance.